A Case of Advanced-Stage Sclerosing Cholangitis with Autoimmune Pancreatitis not Responsive to Steroid Therapy - Nakazawa, Takahiro; Naitoh, Itaru; Ando, Tomoaki; Hayashi, Kazuki; Okumura, Fumihiro; Miyabe, Katsuyuki; Yoshida, Michihiro; Ohara, Hirotaka; Joh, Takashi (JOP. Journal of the Pancreas, 2016)
Context Autoimmune pancreatitis and sclerosing cholangitis associated with autoimmune pancreatitis respond well to steroid therapy. Some criteria used for the differential diagnosis of autoimmune pancreatitis and sclerosing cholangitis with autoimmune pancreatitis include the response to a steroid trial. Case report A 68-year-old woman was diagnosed as having type 3 sclerosing cholangitis with autoimmune pancreatitis four years after clinical onset. Seven years after clinical onset, imaging findings revealed multiple pancreatic stones in an atrophic pancreas, stenosis of the main pancreatic duct in the head of the pancreas and upstream dilatation and a longer stretch of stenosis in the hilar hepatic region. We tried steroid therapy in an attempt to ameliorate stenosis of both the bile duct and the pancreatic duct and prevent further progression. Neither lesion responded to steroid therapy. Conclusion Advanced-stage sclerosing cholangitis with autoimmune pancreatitis may sometimes be unresponsive to steroid therapy, and this should be borne in mind when attempting a steroid trial for the diagnosis of sclerosing cholangitis with autoimmune pancreatitis. Early administration of steroid is important for the prevention of disease progression. Image: ERCP by using a balloon catheter showing a longer stretch of stenosis in the hilar hepatic region.